An Analysis Code-Mixing Found In Social Media Twitter: Sociolinguistic Approach - Chika, Anastasia Chika Alvina; Nurma Dhona Handayani (Publiciana, 2022)
In this millennial era, many young people mix Indonesian with other languages. The most common is the mixing of Indonesian and English. This mixing language can be find in the social media like Twitter. In this platform, people can post everything they want and use any language. This research discusses English code mixing on Indonesian Twitter. Code mixing is the use of two language or more by inserting one language elements into another language element in one sentence. The purpose of this research is to discover the types of code mixing used by Indonesians. A descriptive qualitative method is applied to analyze the data using Muysken theory. The data source used in this research is social media Twitter. The data in the analysis is in the form of posts on Twitter. The data analysis technique in this research used the note-taking technique. The results of the research show that in postings on Twitter there are several types of code mixing such as alteration, insertion, and congruent lexicalization.